Embriogenesis somatik langsung dan regenerasi planlet kopi arabika (Coffea arabica) dari berbagai eksplan Direct somatic embryogenesis and regeneration of arabica coffee plantlets (Coffea arabica) from different explants - Fetrina OKTAVIA; . SWANTO; Asmini BUDIANI (INDONESIAN RESEARCH INSTITUTE FOR BIOTECHNOLOGY AND BIOINDUSTRY, 2003)
SummaryTissue culture technique for arabica coffeefaces some problems, mainly in plantletsregeneration from cultured explants. Theobjectives of this experiment were to examine theeffect 2,4-D and 2-ip combinations on somaticembryogenesis and regeneration of arabicacoffee from several different explants. Basalmedium used in this experiment was MS mediumwith ½ concentration of macro and micro salts.Experiment to induce primary somatic embryos(SE) was arranged in factorial randomizedcomplete design with 10 repeats. The first factorwas the type of explants, leaf, epicotyl, hipocotyland root explants. The second factor was plantgrowth regulator i.e. combination of 1  M 2,4-Dwith 5, 10, 15, 20  M and combination of 5  M2,4-D with 5, 10, 15 and 20  M 2-ip. To multiplySE, secondary SE was induced from primary SEon medium containing combination of 0.6  MIAA and 13.3; 17.8 and 22.2  M BAP.Cotyledonary SE were germinated on mediacontaining GA 3 (0, 5, 10 and 15  M), and thenregenerated on medium free of growth regulator.Plantlets with 4-5 leaf pairs were transfered intothe soil medium for acclimatization. The resultsshow that primary SE can be induced from allexplants with the highest frequency on mediumcontaining 1  M 2,4-D and 15  M 2-ip.Induction of primary SE, in leaf explant wasmore effective than other explants. Mediumcontaining 0.6  M IAA and 22.2  M BAP gavethe highest percentage of SE multiplication i.e.52.6% with average SE number of 6.25. Plantletsregeneration can be conducted by culturing SEon maturation medium free of growth regulatorfor one month followed by germinating onmedium containing GA 3 , and then culturing onmedium free of growth regulator again. Thehighest percentage of germinated embryos wasobtained after three weeks and six weekscultured in the medium containing 5  M GA 3 , i.e49% and 90.15 respectively. From total plantletsobtained, 75% of them were normal. Sixtypercents of the young plants grew well in thegreenhouse.RingkasanTeknik kultur jaringan tanaman kopi arabikamasih menghadapi beberapa kendala terutamapada tingkat regenerasi planlet dari eksplan yangdikulturkan. Penelitian ini bertujuan untukmengetahui pengaruh kombinasi 2,4-D dan 2-ipterhadap embriogenesis somatik dan regenerasikopi arabika dari berbagai eksplan. Media dasaryang digunakan adalah medium MS ½konsentrasi garam makro dan mikro. Percobaaninduksi embrio somatik (ES) primer disusunmenurut rancangan acak lengkap faktorial dengan10 ulangan. Faktor pertama adalah jenis eksplan,erdiri atas daun, epikotil, hipokotil dan akar invitro. Faktor kedua adalah zat pengatur tumbuh,yaitu kombinasi 1 M 2,4-D dengan 5, 10, 15dan 20M 2-ip, serta kombinasi 5 M 2,4-Ddengan 5, 10, 15 dan 20 M 2-ip. Untuk mem-perbanyak jumlah ES yang didapatkan, dilakukaninduksi ES sekunder dari ES primer pada mediumyang mengandung kombinasi 0,6 M IAA dan13,3; 17,8 dan 22,2 M BAP. ES fase kotiledonkemudian dikecambahkan pada medium yangmengandung GA 3 (0, 5, 10 dan 15 M) danselanjutnya diregenerasikan pada medium tanpazat pengatur tumbuh. Planlet yang mempunyai4-5 pasang daun dipindahkan ke medium tanahuntuk aklimatisasi. Hasil yang diperolehmenunjukkan bahwa ES primer dapat diinduksipada semua eksplan yang digunakan denganfrekuensi tertinggi pada medium yang me-ngandung 1 M 2,4-D dan 15 M 2-ip. InduksiES primer pada eksplan daun lebih efektifdibandingkan eksplan lainnya. Untuk per-banyakan ES, medium yang mengandung IAA0,6 M dan BAP 22,2 M memberikanpersentase tertinggi pembentukan ES sekunderyaitu 52,6% dengan rata-rata jumlah ES 6,25.Regenerasi planlet dapat dilakukan denganmengkulturkan ES pada medium maturasi tanpazat pengatur tumbuh selama satu bulan, kemudiandikecambahkan dalam medium yang mengan-dung GA 3 , dan selanjutnya dipindah ke mediumtanpa zat pengatur tumbuh kembali.Perkecambahan ES tertinggi diperoleh padamedium dengan penambahan GA 3 5 M yaitu40,9% setelah tiga minggu dan 90,1% setelahenam minggu. Dari total planlet diperoleh 75%planlet normal. Hasil aklimatisasi menunjukkanbahwa 60% bibit mampu bertahan di rumah kaca.